Faecalibacterium prausnitzii-derived outer membrane vesicles reprogram gut microbiota metabolism to alleviate Porcine Epidemic Diarrhea Virus infection - JunHong Xing; TianMing Niu; Tong Yu; BoShi Zou; ChunWei Shi; YingJie Wang; ShuHui Fan; MingHan Li; MeiYing Bao; Yu Sun; KuiPeng Gao; JingJing Qiu; et al. (Microbiome)
Abstract Background The Porcine Epidemic Diarrhea Virus (PEDV) is one of the major challenges facing the global pig farming industry, and vaccines and treatments have proven difficult in controlling its spread. Faecalibacterium prausnitzii (F.prausnitzii), a key commensal bacterium in the gut, has been recognized as a promising candidate for next-generation probiotics due to its potential wide-ranging health benefits. A decrease in F.prausnitzii abundance has been associated with certain viral infections, suggesting its potential application in preventing intestinal viral infections. In this study, we utilized a piglet model to examine the potential role of F.prausnitzii in PEDV infections. Results A piglet model of PEDV infection was established and supplemented with F.prausnitzii, revealing that F.prausnitzii mitigated PEDV infection. Further studies found that outer membrane vesicles (OMVs) are the main functional components of F.prausnitzii, and proteomics, untargeted metabolomics, and small RNA-seq were used to analyze the composition of OMVs. Exhaustion of the gut microbiota demonstrated that the function of Fp. OMVs relies on the presence of the gut microbiota. Additionally, metagenomic analysis indicated that Fp. OMVs altered the gut microbiota composition, enhancing the abundance of Faecalibacterium prausnitzii, Prevotellamassilia timonensis, and Limosilactobacillus reuteri. Untargeted metabolomics analysis showed that Fp. OMVs increased phosphatidylcholine (PC) levels, with PC identified as a key metabolite in alleviating PEDV infection. Single-cell sequencing revealed that PC altered the relative abundance of intestinal cells, increased the number of intestinal epithelial cells, and reduced necroptosis in target cells. PC treatment in infected IPEC-J2 and Vero cells alleviated necroptosis and reduced the activation of the RIPK1-RIPK3-MLKL signaling axis, thereby improving PEDV infection. Conclusion F.prausnitzii and its OMVs play a critical role in mitigating PEDV infections. These findings provide a promising strategy to ameliorate PEDV infection in piglets. Video Abstract Graphical Abstract